Digital Transformation of Education through Problem-Based Learning: Models, Applications, andOutcomes (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
This paper explores the integration of problem-basedlearning within the digital transformation of educationalframeworks, examining various models, their practicalapplications, and the resulting educational outcomes. Itanalyzes how this pedagogical approach, which emphasizesstudent-centered learning through real-world problems, isbeing adapted to virtual environments to foster higher-orderthinking skills and prepare students for complex, evolvingchallenges. Specifically, this study investigates howuniversities are leveraging digital tools to implement ProblemBased Learning in ways that were previously unfeasible intraditional face-to-face settings, thereby enhancing learningengagement and knowledge acquisition. The paper furtherdelves into the challenges and opportunities presented bythis digital shift, highlighting how successful implementationrequires a deep understanding of both pedagogical principlesand technological capabilities to facilitate meaningful learningexperiences. This exploration extends to the impact of digitalPBL on critical employability skills, such as critical thinkingand problem-solving, which are crucial for preparinggraduates for dynamic industry needs. Ultimately, the paperaims to delineate a comprehensive understanding of howdigitally-transformed PBL not only enhances academiccompetencies but also cultivates essential professionalattributes necessary for navigating the complexities of themodern workforce.
Keywords: Digital Transformation, Problem-Based Learning, Higher Education, Employability Skills, Critical Thinking, Gamification.